Assessment of Biochemical Parameters of Mothers and Neonates in Cigarette Smoke Exposure: A Cross Sectional Study from Vidarbha Region, India - Prajakta Warjukar; Ankush Mohabey; Gangaram Bhadarge; Pratibha Dawande; Roshan Kumar Jha (Advancement and New Understanding in Medical Science Vol. 8, 2024)
Introduction: Vitamin D is a nutrient that is needed for bone growth and processing. Vitamin D and calcium are extremely important during certain stages of life, such as the baby’s development, childhood, childhood and adolescence, breastfeeding, lactation, and old age. Vitamin D and calcium deficiency have severe implications at this time. Maternal nutrition status is the most significant determinant of the nutritional status of a newborn and other maternal well-being and fertility outcomes. Aim: This Study aims to analyse the biochemical parameters of mothers and neonates in cigarette smoke exposure in the Vidharbha region. Material and Methods: Pregnant non-smoker women who were referred to a Tertiary Health Care Hospital in Vidarbha region were selected for the study.. Distribution was done on the basis of their history of exposure to tobacco smoke; 54 subjects were exposed to tobacco smoke and 54 subjects were not exposed to tobacco smoke. Result: Maternal Vitamin D was highly significantly low in pregnant females exposed to tobacco smoke (13.71± 4.33 ng/ml) as compared to non –exposed pregnant females (21.02 ± 4.96 ng/ ml) ((p-value <0.0001) Based on self-reported exposure, maternal serum calcium levels was highly significantly low in exposed females (8.43 ± 0.64mg/dl) than in non-exposed females (10.04 ± 0.72mg/dl) (p <0.0001). There was no significant difference in serum Parathormone level and serum phosphorus levels between the 2 groups (P- value for Parathormone- 0.2163 and for Phosphorus-0.1904. Alkaline phosphatase levels in the exposed group were found to be significantly high than the non-exposed group (p = 0.0129). In neonates of mothers exposed to tobacco smoke, cord blood serum Vitamin D and Calcium levels were significantly low as compared to neonates of non- exposed mothers. Conclusion: The findings showed that, second-hand smoke consumption had a detrimental effect on pregnant women. In mothers and neonates exposed to the tobacco smoke, serum Vitamin D levels and Calcium level s were significantly lowas compared to the non exposed mothers and neonates. These studies recommend steps should be taken to minimize exposure to nicotine during pregnancy and to improve the use of vitamin D and calcium supplements during pregnancy, taking into account the risk to women during this crucial time of life and the effects on the well-being of the infant.